Case report of dengue shock syndrome with decrease of consciousness, sepsis, and clinical tuberculosis - Jane Rosaline Sutanto; Zuriah Hidajati (Institute of Computer Science (IOCS), 2022)
Dengue is a disease caused by the dengue virus, which is a classification of the Flavivirus group. The Aedes mosquito group transmits this virus. Dengue infection can provide a diverse clinical spectrum. This is a type of qualitative research with a case study approach. The case was conducted at the K.R.M.T. Wongsonegoro Regional Hospital, Semarang. Retrieval of data used primary data and secondary data. Case management was done following the Standard Operating Procedures set by the hospital. Data analysis was conducted by comparing cases with review literature sourced from articles or other scientific sources. The case study results pointed out that a girl was brought by her parents to the emergency room at R.S.D. K.R.M.T. Wongsonegoro on April 18, 2022, at 13.30 WIB as a referral patient from the Public Health Center with complaints of seizures and shortness of breath. The child's condition was monitored by experiencing changes on the eleventh day in the PICU Room.